QUEUING ANALYSIS OF CAR SERVICING CUSTOMERS USED SINGLE CHANNEL MODEL AND KENDALL’S NOTATION IN PT. ARMADA MOBIL PURWOKERTO - Tugiyono Tugiyono; Ida Betanursanti (Spektrum Industri, 2013)
This study aims to identify the customer’s problem queue, specify the model queue, the arrival and customer service frequency distributions at PT. Armada Mobil Purwokerto. Methods of the research conducted by observing and measuring directly the research object, the data from the study was calculated according to the theory of queues. The result appropriate to single channel queuing model Poisson distribution of the arrivals, exponential distribution of the time service. The characteristized of Kendall’s notation is M/M/3/3/571. Key words: single channel, Poisson distribution, dan Kendall’s notation